2014
DOI: 10.1111/resp.12294
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic changes in pulmonary hypertension in patients with interstitial lung disease treated with PDE‐5 inhibitors

Abstract: Our data suggest that treatment with PDE-5 inhibitors improves pulmonary haemodynamic patients with PH secondary to ILD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 30 publications
(91 reference statements)
1
24
0
4
Order By: Relevance
“…Sildenafil has also been found to improve quality of life in these patients [101]. In a further study, sildenafil and tadalafil were used for the treatment of PH in IPF and hypersensitivity pneumonitis (HP) [102]. After a minimum 3 months of treatment, an increase in cardiac index (CI) and decrease in PVR were observed but 6MWT and BNP level did not change significantly.…”
Section: Treatmentmentioning
confidence: 99%
“…Sildenafil has also been found to improve quality of life in these patients [101]. In a further study, sildenafil and tadalafil were used for the treatment of PH in IPF and hypersensitivity pneumonitis (HP) [102]. After a minimum 3 months of treatment, an increase in cardiac index (CI) and decrease in PVR were observed but 6MWT and BNP level did not change significantly.…”
Section: Treatmentmentioning
confidence: 99%
“…The clinical studies performed both in DPLD and in PH-DPLD confirmed that sildenafil did not carry a significant risk of worsening of oxygenation [26,27,39,45].…”
Section: Is the Treatment Efficacy Related To The Class Of Pah-specifmentioning
confidence: 65%
“…Zimmerman et al [45] found significant haemodynamic improvement in 10 ILD patients treated with 5PDEi in the open label observational study.…”
Section: Rationale For Pah-specific Drugs Use In Ph-dpldmentioning
confidence: 94%
See 1 more Smart Citation
“…Right heart catheterization was performed as described previously ( n = 19) . Pulmonary function testing and blood gas analysis were performed according to the European Respiratory Society Guidelines .…”
Section: Methodsmentioning
confidence: 99%